Troubleshooting Analysis of CVT (Continuously Variable Transmission) System on Honda Beat Motorcycles - Rinasa Agistya Anugrah (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2022)
There are about 87% of motorcycles used by motorists on the streets are automatic type motorcycles which are dominated by Honda Beat. Seeing the interest of the world community about their interest in automatic motorcycles, it is necessary to conduct research to analyze the CVT (Continuously Variable Transmission) system on this motorcycle. The method used in this research is the troubleshooting analysis method. Troubleshooting is a method for observing symptoms, diagnosing damage, conducting inspections and measurements, identifying damage based on the results of inspections and measurements, and determining corrective steps if repairs must be made. The results of this study are recommendations for troubleshooting steps on the Honda Beat CVT system. With this troubleshooting step, technicians have a reference to carry out maintenance and repair of Honda Beat automatic motorcycles, especially on the CVT system. Terdapat sekitar 87% sepeda motor yang digunakan pengendara dijalanan adalah sepeda motor tipe matic yang didominasi oleh Honda Beat. Melihat animo masyarakat dunia tentang minat mereka terhadap sepeda motor matic maka perlu dilakukan penelitian untuk menganalisis sistem CVT (Continuously Variable Transmission) pada sepeda motor ini. Metode yang digunakan dalam penelitian ini adalah metode analisis troubleshooting. Troubleshooting adalah metode untuk mengamati gejala, mendiagnosis adanya kerusakan, melakukan pemeriksaan dan pengukuran, mengidentifikasi kerusakan berdasarkan hasil pemeriksaan dan pengukuran, serta menentukan langkah perbaikan jika harus dilakukan perbaikan. Hasil dari penelitian ini adalah rekomendasi langkah troubleshooting pada sistem CVT Honda Beat. Dengan Langkah troubleshooting ini para teknisi memiliki acuan untuk melaksanakan perawatan dan perbaikan sepeda motor matic Honda Beat khususnya pada sistem CVT.